Mechanisms and roles of muscarinic activation in guinea-pig adrenal medullary cells - Inoue, Masumi (American Physiological Society, 2012)
Muscarinic receptors are expressed in the adrenal medullary (AM) cells of various mammals, but their physiological roles are controversial. Therefore, the ionic mechanism for muscarinic receptor-mediated depolarization and the role of muscarinic receptors in neuronal transmission were investigated in dissociated guinea-pig AM cells and in the perfused guinea-pig adrenal gland. Bath application of muscarine induced an inward current at −60 mV. This inward current was partially suppressed by quinine with an IC(50) of 6.1 μM. The quinine-insensitive component of muscarine-induced currents changed the polarity at −78 mV and was inhibited by bupivacaine, a TWIK-related acid-sensitive K(+) (TASK) channel inhibitor. Conversely, the current-voltage relationship for the bupivacaine-insensitive component of muscarine currents showed a reversal potential of −5 mV and a negative slope below −40 mV. External application of La(3+) had a double action on muscarine currents of both enhancement and suppression. Immunoblotting and immunocytochemistry revealed expression of TASK1 channels and cononical transient receptor potential channels 1, 4, 5, and 7 in guinea-pig AM cells. Retrograde application of atropine reversibly suppressed transsynaptically evoked catecholamine secretion from the adrenal gland. The results indicate that muscarinic receptor stimulation in guinea-pig AM cells induces depolarization through inhibition of TASK channels and activation of nonselective cation channels and that muscarinic receptors are involved in neuronal transmission from the splanchnic nerve.